User Interface Design Using Lean UX on Hello Work Website at Labor Office of Kabupaten Pasuruan - Adhipratama, Yoga; Sagirani, Tri; Kartikasari, Puspita (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Hello Work is a website owned by The Labor Office of Kabupaten Pasuruan (Disnaker) that has been developed for the labors from Pasuruan. By using Hello Work, the job seekers could find some companies or firms which opening the job vacancy that fit for job seeker’s criteria. But the survey’s result has proven still so many job seekers has problems at using Hello Work, especially on user interface for sign up process and less user friendly for mobile phone. As the described problem, the solution is to create a user interface by using Lean UX methode which composed by four stages, that are Declaring Assumption, Create an MVP, Run an Experiment, and Feedback and Research. And the result is a website prototype for desktop and mobile phone with seven improvement, that are a new dashboard layout, new login process, news column, user friendly sign-up process, new labor’s dashboard, and mobile version of Hello Work with improvement of the mean score from 3.016 for existing website to 3.54 for website prototype.